THE PROMINENT SCHOLAR OF JADID PEDAGOGY - Rakhmonova Mehriniso Toshpulotovna (International Journal of Literature and Language Studies, 2026)
The article examines the issues of morality in the education of a comprehensively developed personality, one of the most pressing problems of our time. The article examines the role of morality in the formation of personality, the factors of its application and the ways of implementing this issue, and also highlights the life path of Ahmad Donish, a supporter of the Jadidism movement.Ahmad Donish is at the forefront of new educational theory. In his work,